COLLOQUIAL OF AMBON MALAY LANGUAGE AT GALALA YOUNG MEN, SIRIMAU DISTRICT (A SOCIOLINGUISTICS STUDY) - Sinta Risakotta (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2018)
Colloquial speech at young men in Galala always creates casual conversation, moreover in a young men society, Colloquial is used as a game to satirize or mock somebody and the words in the speech are created and defined by themselves. At Galala young men’s Colloquial, Ambon Malay language is always exist to revive the situation of the conversation. The purpose of this research is to describe Colloquial of Ambon Malay language at Galala young men, Sirimau district, with the first benefit to student that is to increase the knowledge of Colloquial conversation, and the second benefit to the further researcher as preliminary study about the theory and Colloquial phenomenon and also as a reference to the further researcher. This article is begun with the explanation of relevant theoretical basis such as: Colloquial; statement form, question, command in Colloquial of Ambon Malay language at Galala young men; the function of the usage of ColloquialAmbon Malay language of Galala young men; Ambon Malay language; sociolinguistics; Colloquial; the condition of socioinguistic in Indonesia and is ended with socioinguistics study.